Identification and quantitative analyses of microRNAs located in the distal axons of sympathetic neurons - Natera-Naranjo, Orlangie (Cold Spring Harbor Laboratory Press, 2010)
microRNAs (miRNAs) constitute a novel class of small, noncoding RNAs that act as negative post-transcriptional regulators of gene expression. Although the nervous system is a prominent site of miRNA expression, little is known about the spatial expression profiles of miRNAs in neurons. Here, we employed compartmentalized Campenot cell culture chambers to obtain a pure axonal RNA fraction of superior cervical ganglia (SCG) neurons, and determined the miRNA expression levels in these subcellular structural domains by microarray analysis and by real-time reverse-transcription polymerase chain reaction. The data revealed stable expression of a number of mature miRNAs that were enriched in the axons and presynaptic nerve terminals. Among the 130 miRNAs identified in the axon, miR-15b, miR-16, miR-204, and miR-221 were found to be highly abundant in distal axons as compared with the cell bodies of primary sympathetic neurons. Moreover, a number of miRNAs encoded by a common primary transcript (pri-miRNA) were differentially expressed in the distal axons, suggesting that there is a differential subcellular transport of miRNAs derived from the same coding region of the genome. Taken together, the data provide an important resource for future studies on the regulation of axonal protein synthesis and the role played by miRNAs in the maintenance of axonal structure and function as well as neuronal growth and development.